Contagion risk in the Danish Interbank market - Elin Amundsen; Henrik Arnt (Danmarks Nationalbank, 2005)
This paper uses records of payments in the Danish large value payment system to compute a unique, high-frequency data set on bilateral exposures between banks. The risk of contagion in the Danish interbank market is subsequently analysed using this data set. It is found that the risk of financial contagion due to an unexpected failure of a major bank is very limited. This applies even when banks are assumed to loose all their exposure, i.e. a loss given default of 100 per cent. Where contagion is identified, it affects only smaller banks and no further knock-on effects are found.
Keywords: 330; Geldmarkt; Bankenkrise; Schätzung; Dänemark